Exploring the Ecological Roles and Conservation Needs of Deep-Sea Microbial Life: A Short Review - Tadi, Lakshmi Jyothi; Naaz, Shazia (Research Perspectives of Microbiology and Biotechnology Vol. 9, 2025)
Purpose: This review explores the ecological significance and conservation needs of microbial communities in deep-sea environments. It aims to underscore the critical roles of microorganisms in nutrient cycling, carbon sequestration, and sustaining complex food webs in one of Earth's least understood frontiers. Methods: The study synthesizes existing research on the biodiversity and ecological functions of deep-sea microbes, emphasizing their adaptation to extreme conditions such as high pressure, low temperature, and absence of sunlight. Techniques in biotechnology and bioinformatics that enable the exploration and monitoring of these communities are highlighted. Findings: Deep-sea microbes are pivotal in maintaining the stability of marine ecosystems, contributing to organic matter recycling and chemical balance. The review also discusses the symbiotic relationships these microbes form with other deep-sea organisms, particularly at hydrothermal vents and cold seeps, which are crucial for the survival of diverse macroscopic life forms. Conclusions: Despite their significance, deep-sea microbial communities face threats from human activities such as mining, pollution, and the effects of climate change. Conservation efforts are urgently needed to protect these critical ecosystems. The establishment of marine protected areas and the advancement of microbial research are essential steps toward preserving the biological wealth of the deep sea for future generations.